Who Does the Talking Here? The Impact of Gender Composition on Team Interactions - Hardt, David; Mayer, Lea; Rincke, Johannes (Management Science, 2024)
We analyze how the gender composition of teams affects team interactions. In an online experiment, we randomly assign individuals to gender-homogenous or gender-mixed teams of four. Teams meet in an audio chat room and jointly work on a team task that is gender-neutral in terms of individual productivity. By design, effects on team performance can only work through communication. We find that all-male teams communicate more than all-female teams and outperform teams of both alternative gender compositions. In mixed teams, men strongly dominate the team conversation quantitatively. Considering the ranking in terms of communication shares in mixed teams, we document that high-skilled men talk the most, followed by low-skilled men. High-skilled women talk more than low-skilled women, but much less than low-skilled men. We conclude that gender composition significantly impacts the way how teams exchange informatio